Ruptured Intracranial Mycotic Aneurysm in Infective Endocarditis: A Natural History - Isabel Kuo; Theodore Long; Nathan Nguyen; Bharat Chaudry; Michael Karp; Nerses Sanossian (Case Reports in Medicine)
Mycotic aneurysms are a rare cause of intracranial aneurysms that develop in the presence of infections such as infective endocarditis. They account for a small percentage of all intracranial aneurysms and carry a high-mortality rate when ruptured. The authors report a case of a 54-year-old man who presented with infective endocarditis of the mitral valve and acute stroke. He subsequently developed subarachnoid hemorrhage during antibiotic treatment, and a large intracranial aneurysm was discovered on CT Angiography. His lesion quickly progressed into an intraparenchymal hemorrhage, requiring emergent craniotomy and aneurysm clipping. Current recommendations on the management of intracranial Mycotic Aneurysms are based on few retrospective case studies. The natural history of the patient's ruptured aneurysm is presented, as well as a literature review on the management and available treatment modalities.